India's participation in global value chains and some implications for economic and social upgrading: A case study of the automobile sector - Praveen K. Jha; Dinesh Kumar (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2021)
This paper maps the integration of India's automobile sector in the context of the structural transformation of contemporary capitalism, in particular with reference to what is variously described as Global Commodity Chains, Global Value Chains, Global Supply Chains etc. It explores the multiple dimensions of economic and social upgrading within the Indian auto sector as a consequence of its deepening participation in these 'chains'. The paper is divided into six sections. Section 1 provides a brief introduction; Section 2 gives a brief profile of the Indian automobile sector and also discusses briefly its major constituents, namely, original equipment manufacturers (henceforth OEM) and auto component segment, and their geographical distributions; Section 3 provides an overview of the data and methodology; Section 4 analyses India's GVCs participation, using a couple of indicators, and examines some aspects of economic and social upgrading in both the organised and unorganised sectors; Section 5 flags a few recent policies and plans adopted by India's central government in this industry; Section 6 concludes the chapter with a recap of major findings.
Keywords: F66; L62; 330; Global Value Chains; Automobile Sector; Employment; Wages; Neoliberal Policy